Development of the Service Model for Elderly Quality Service of Primary Care Unit in Bangkok, Thailand - WIMONTHADA, Kesarin; THALERNGPOL2, Praopitcha; WORAPHATTHIRAKUL3, Peerapong; CHITTAPHONE4 , Namfonh; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purposes of this research paper were: 1) to study the development of the service model for elderly quality service for private primary care unit in Bangkok: 2) to study the factors affecting the development of the service model for elderly quality service for private primary care unit in Bangkok: and 3) to suggest the development of the service model for elderly quality service for private primary care unit in Bangkok. It was qualitative research using in-depth interviews. The key informants consisted of 25 people from the government sector, private primary care unit, and elderly to obtain information according to research objectives, focus on fact-finding, and bring in a systematic, rational, and theoretical conclusion and based on theory. The results showed that development of the service model for elderly quality service for private primary care unit in Bangkok by creating health insurance through participation mechanism, building knowledge and understanding of rights and duties, along with providing a convenient and comprehensive service system with a focus on the sustainability of the health insurance system. The finding is based on structural changes in population, politics, economy, technology, natural resources and environment, and epidemiology of diseases that may affect the quality of life of people in society on long-term investment in the public health system. It was suggested this research of the budgetary management focused on efficiency, effectiveness and value need to focus and drive health policy for creating equality in society.